The Romantic Nightingale between Coleridge’s Divergence and Keats’ Adherence: A comparative Study between Coleridge’s ‘The Nightingale’ and Keats’ ‘Ode to a Nightingale’ (Journal of the College of Education for Women, 2019)
‘Ode to a Nightingale’(1819) is a typical poem of a Romantic poet like John Keats, but‘The Nightingale’(1798) is an uncharacteristic poem of a Romantic poet like Coleridge.The paper proposes a comparison between Coleridge’s ‘The Nightingale’ and Keats’‘Ode to a Nightingale’.Coleridge’s poem diverges from the Romantic norm; it carries somecharacteristics new to Romantic poetry like the realistic and objective portrayals of nature andthe nightingale, while Keats’ poem adhere to the characteristics of Romantic poetry; itportrays nature and the nightingale subjectively and unrealistically. Coleridge’s poem is verymuch influenced by the scientific approaches to environment, and natural history which haveemerged at the end of the 18th C., and this influence has led Coleridge to diverge from theRomantic norm, while Keats’ Ode does not react to this emergence, it preserves the prominentfeatures of Romantic poetry, though it follows Coleridge’s poem in not more than twenty oneyears.The paper is divided into two sections, and a conclusion. The first section, ‘Coleridge’sDivergence from the Romantic Norm’starts with presenting Coleridge as the conventionalRomantic poet who is not different from Keats nor any other major Romantic poet indepicting nature and the nightingale in most of his poems, with the aim to highlight hissudden divergence from his Romantic line in ‘The Nightingale’. The part moves to discussColeridge’s abandonment of the characteristics previously mentioned of Romantic poetry inhis ‘The Nightingale’ through his realistic and objective approaches to the nightingale whichcome as a reaction to the occurrence of natural and ornithological studies.The second section, ‘Keats’ Adherence to the Romantic Norm’ discusses Keats’preservation of the prominent characteristics of Romantic poetry in his ‘Ode to a Nightingale’like escapism, allusion, imitation of Milton, the unrealistic and subjective approaches tonature and the nightingale,and degenderization of the nightingale which all point out Keats’disregard for the occurrence of scientific approaches to nature and the bird at the time.Finally, the conclusion sums up the findings of the study.